Plants and empire : colonial bioprospecting in the Atlantic world - Schiebinger, Londa L. (Harvard University Press, 2004)
A rich history of discovery and loss, 'Plants and Empire' explores the movement, triumph and extinction of knowledge in the course of encounters between Europeans and the Caribbean populations.